Al-Bukhary Intellectul Genealogy: Tracing The Authority of An Hadith and Fiqh - Muh. Fathoni Hasyim (Universitas Islam Negeri Antasari Banjarmasin, 2019)
Abstract: This article aims to reveal the authority of al-Bukhary as intellectul figures who have independence in dul scientific authority. He is often assumed as an expert of hadith only. In fact, as a collector of hadiths, he studied those hadiths deeper as a source of law which produced ijtihad products that are different compared to the predecessors. Therefore, some people argue that he is not only an expert of hadith but also a mujtahid (fiqh expert). In this context, it is interesting to explore the intellectul genealogy of al-Bukhary. The findings of this study prove that he succeeded in occupying a high position as an expert of both hadith and fiqh by interacting with many scholars from various regions. This interaction form his intellect which worthy of being called the absolute mujtahid. Al-Bukhary succeeded in exploring fiqh thoughts based on his extensive and deep mastery of hadiths. Through his ijtihad products, al-Bukhary had built a dynamic and authoritative tradition of Islamic intellectul treasure. Abstrak: Artikel ini bertujuan untuk mengungkap otoritas al-Bukhary sebagai tokoh intelektual yang memiliki independensi dalam otoritas ilmiah. Ia sering dianggap sebagai ahli hadis saja. Bahkan, sebagai pengumpul hadis, ia mempelajari hadits-hadits tersebut sebagai sumber hukum yang menghasilkan produk ijtihad yang berbeda dibandingkan dengan para pendahulunya. Oleh karena itu, beberapa orang berpendapat bahwa ia bukan hanya ahli hadits tetapi juga seorang mujtahid (ahli fiqh). Dalam konteks ini, menarik untuk mengeksplorasi silsilah al-Bukhary yang intelek. Temuan penelitian ini menunjukkan bahwa ia memiliki otoritas independen sebagai ahli hadits dan fiqh. Otoritas tersebut merupakan hasil interaksi dengan banyak ulama dari berbagai wilayah. Interaksi guru-murid dalam upaya kodifikasi hadis ini membentuk kecerdasannya yang layak disebut mujtahid mutlak. Al-Bukhary berhasil mengeksplorasi pemikiran fiqh berdasarkan penguasaan haditsnya yang luas dan mendalam. Melalui produk ijtihadnya, al-Bukhary telah membangun tradisi yang dinamis dan otoritatif dari khazanah intelektual Islam.